A docência compartilhada: um olhar para a ação de professores dos anos iniciais do ensino fundamental e sua relação com o trabalho coletivo - Mazer, Inês Maria Silva Barros (2024)
The present work was inspired by the Historical-Cultural theory and its general objective is to understand how the development of Shared Teaching occurs in the "Todos Juntos" Project and its relationship with Collective Work. To this end, the main question of this research is: "how can the development of pedagogical actions in Shared Teaching be related to Collective Work?". As specific objectives, we seek to identify the constituent characteristics of Shared Teaching and compare them with the elements of Collective Work. The object of study, therefore, is collective work in shared teaching. According to Hochnadel and Conte (2019), Shared Teaching consists of a shared action between two teachers in the classroom. Collective Work, for Makarenko (1977), occurs through the development of coordinated and organized actions with responsibility for the common benefit. In this sense, the collective is understood as a living organism of a society. In addition to these concepts, "dialogue" in this research is understood as in the Freirean perspective, as the force that drives critical and problematizing thinking, together with what Bohm (2005) establishes about the purpose of dialogue in going through the thought process to change the way it happens collectively. In relation to the instrument for constructing information, the Focus Group technique was used as a vehicle that provided opportunities for discussions relevant to the subjects studied here. This technique, in qualitative research, allowed group analysis, considering the group of participants, making it possible to obtain information on the proposed topic. The results of this research show that there are movements in the development of pedagogical actions in Shared Teaching that can lead to collective teaching work, although we conclude that we were unable to determine full support of the collective work in the "Todos Juntos" project, due to its duration. duration and other limitations such as the subjects, their activities and material conditions. Thus, after completing this research, we considered the construction of an educational product that would bring the relationships established between the characteristics of Shared Teaching and the elements of Collective Work with the aim of explaining a path for the construction of collective teaching work. This product is intended for everyone interested in the topic, especially teachers and other professionals who consider humanization as the key to their actions and propose to join efforts to build the collective as the strength, union and transformation necessary for education.